Application of Digital Communication to Increase The Tourism Promotion in Dayeuh Kolot Village, Subang - Firmansyah Firmansyah; Tazkiya Fadhilah; Aryana Catur; Ervana Nurmelia; Raihan Rachmansyah (MediaTor (Jurnal Komunikasi), 2021)
The development of tourism villages in several areas including West Java needs to be encouraged by digital promotion. In the internet era, digital communication is mandatory for stakeholders in the economic sector, including tourism stakeholders. Based on this, tourism development through digital communication needs to be done to encourage tourist attraction. This research describes the development of tourism promotion through digital communication in Dayeuh Kolot village in several stages. The research method uses case studies with data collection techniques through observation, interviews, and documentation to measure the stages of digital communication application. Observations were made at the stages of digital communication application, namely in the stages of preparation, implementation, and evaluation of digital development in the period of July until December 2020. Interviews were conducted with tourism organizer stakeholders, namely the village government, BUMDES, and people who were members of the Keciwis community to get an overview of promotion development Meanwhile, the documentation data is obtained statistically as a comparison before and after the development of digital promotion. The results showed that the knowledge and skills of tourism stakeholders had significantly increased, especially in the management of social media and digital communication for tourism marketing.